The Political Economy of the Hospital in History - Doyle, Barry (University of Huddersfield Press, 2020)
The modern hospital is at once the site of healing, the locus of medical learning and a cornerstone of the welfare state. Its technological and infrastructural costs have transformed health services into one of today's fastest growing sectors, absorbing substantial proportions of national income in both developed and emerging economies. The aim of this book is to examine this growth in different countries, with a main focus on the twentieth century, and also with a backward glance to earlier shaping forces. It will explore the hospital's economic history, the relationship between public and private forms of provision, and the political context in which health systems were constructed. The collection advances the historical world map of different hospital models, ranging across Spain, Brazil, Germany, East and Central Europe, Britain, the United States and China. Collectively, these comparative cases illuminate the complexities involved in each country and bring new historical evidence to current debates on health care organisation, financing and reform.